Role of Autophagy and Pyroptosis in Intervertebral Disc Degeneration - Wang Z; Li X; Yu P; Zhu Y; Dai F; Ma Z; Shen X; Jiang H; Liu J (Dove Medical Press, 2024)
Zhiqiang Wang,* Xiaochun Li,* Pengfei Yu,* Yu Zhu, Feng Dai, Zhijia Ma, Xueqiang Shen, Hong Jiang, Jintao Liu Department of Orthopedic Surgery, Suzhou TCM Hospital Affiliated to Nanjing University of Chinese Medicine, Suzhou, 215009, People's Republic of China*These authors contributed equally to this workCorrespondence: Jintao Liu, Department of Orthopedic Surgery, Suzhou TCM Hospital Affiliated to Nanjing University of Chinese Medicine, No. 18 Yangsu Road, Canglang New Town, Suzhou, 215009, People's Republic of China, Email okdoctor2@163.comAbstract: Intervertebral disc degeneration is a chronic degenerative disease caused by the interaction of genetic and environmental factors, mainly manifested as lower back pain. At present, the diagnosis of intervertebral disc degeneration mainly relies on imaging. However, early intervertebral disc degeneration is usually insidious, and there is currently a lack of relevant clinical biomarkers that can reliably reflect early disease progression. Pyroptosis is a regulatory form of cell death triggered by the activation of inflammatory bodies and caspase, which can induce the formation of plasma membrane pores and cell swelling or lysis. Previous studies have shown that during the progression of intervertebral disc degeneration, sustained activation of inflammasomes leads to nuclear cell pyroptosis, which can occur in the early stages of intervertebral disc degeneration. Moreover, intervertebral disc nucleus pulposus cells adapt to the external environment through autophagy and maintain cellular homeostasis and studying the mechanism of autophagy in IDD and intervening in its pathological and physiological processes can provide new ideas for the clinical treatment of IDD. This review analyzes the effects of pyroptosis and autophagy on IDD by reviewing relevant literature in recent years, in order to explore the relationship between pyroptosis, autophagy and IDD.Keywords: intervertebral disc degeneration, pyroptosis, autophagy